Stabilizing the Native Trimer of HIV-1 Env by Destabilizing the Heterodimeric Interface of the gp41 Postfusion Six-Helix Bundle - Kesavardhana, Sannula (American Society for Microbiology, 2014)
The HIV-1 envelope glycoprotein (Env) is a trimer of gp120-gp41 heterodimers and is essential for viral entry. The gp41 subunit in native, prefusion trimeric Env exists in a metastable conformation and attains a stable six-helix bundle (6-HB) conformation comprised of a trimer of N-heptad repeat (NHR) and C-heptad repeat (CHR) heterodimers, that drives the fusion of viral and cellular membranes. We attempted to stabilize native Env trimers by incorporation of mutations at the NHR-CHR interface that disrupt the postfusion 6-HB of gp41. The mutations V570D and I573D stabilize native Env of the HIV-1 JRFL strain and occlude nonneutralizing epitopes to a greater extent than the previously identified I559P mutation that is at the interface of the NHR trimers in the 6-HB. The mutations prevent soluble-CD4 (sCD4)-induced gp120 shedding and 6-HB formation. In the context of cell surface-expressed JRFL Env, introduction of a previously reported additional disulfide between residues A501 and T605 perturbs the native conformation, though this effect is partially alleviated by furin coexpression. The data suggest that positions 570 and 573 are surface proximal in native Env and that the NHR homotrimeric coiled coil in native Env terminates before or close to residue 573. Aspartic acid substitutions at these positions stabilize native trimers through destabilization of the postfusion 6-HB conformation. These mutations can be used to stabilize Env in a DNA vaccine format. IMPORTANCE The major protein on the surface of HIV-1 is the envelope (Env) glycoprotein. Env is a trimer of gp120-gp41 heterodimers. gp120 is involved in receptor/coreceptor binding and gp41 in the fusion of viral and cellular membranes. Like many other viral fusion proteins, the gp41 subunit in native trimeric Env exists in a metastable conformation. gp41 readily forms a stable six-helix bundle (6-HB) conformation comprised of a trimer of N-heptad repeat (NHR) and C-heptad repeat (CHR) heterodimers that drives fusion of viral and cellular membranes. While it is expected that native Env is a good immunogen, its metastability results in exposure of immunodominant nonneutralizing epitopes. In the present study, we stabilize native Env trimers by incorporation of a number of different mutations at the NHR-CHR interface that disrupt the postfusion 6-HB of gp41. The stabilized constructs described here can be incorporated into DNA vaccine candidates.